2006
DOI: 10.1159/000094223
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of a constitutional complex intrachromosomal 4q rearrangement in a patient with multiple congenital anomalies

Abstract: Constitutional Complex Chromosomal Rearrangements (CCRs) are very rare. While the vast majority of CCRs involve more than one chromosome, only seven cases describe CCRs with four or more breakpoints within a single chromosome. Here, we present a patient with multiple congenital anomalies and mental retardation. Array Comparative Genomic Hybridisation (array CGH), FISH and Multicolour Banding FISH revealed a de novo complex rearrangement with two deletions, a duplication and an inversion of 4q. This CCR involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Similar findings have also been reported in several papers describing single patients 11 19 20. The total size of the deletions among 11 patients with phenotypic anomalies (patients 42–47, and 49–53) varies between 0.9 and about 10 Mb.…”
Section: Discussionsupporting
confidence: 89%
“…Similar findings have also been reported in several papers describing single patients 11 19 20. The total size of the deletions among 11 patients with phenotypic anomalies (patients 42–47, and 49–53) varies between 0.9 and about 10 Mb.…”
Section: Discussionsupporting
confidence: 89%
“…Patsalis et al [2004] studied 20 families with apparently balanced translocations and found additional, cryptic aberrations in 15%, which reclassified them as CCRs. This probably also holds true for intrachromosomal rearrangements, but to date, only 10 cases have been described [Romain et al, 1985;Tuck-Muller et al, 1996;Van Esch et al, 2002;Weise et al, 2003;Chudoba et al, 2004;Shim et al, 2004;de Vries et al, 2005;Gajecka et al, 2006;Piovani et al, 2006;Thienpont et al, 2006]. We here report on the detailed characterization of an extremely complex intrachromosomal rearrangement of chromosome 1, revealing 14 different breakpoints, 12 on the p-and two on the q-arm as well as a small deletion of 0.5 Mb on the p-arm.…”
mentioning
confidence: 67%
“…As a result, precise definitions of CCRs and their true complexity can now be better established (Astbury et al 2004; Thienpont et al 2006). An apparent underestimation of the full complexity of CCRs is well demonstrated in patient 1, in whom a complex karyotype was identified, including an inverted insertion of the MDLS region into the middle SMS-REP/LCR17pB block, two microdeletions (terminal and interstitial in 17p12) and a microduplication involving both SMS and CMT1A chromosome regions.…”
Section: Discussionmentioning
confidence: 99%